2014
DOI: 10.1007/s00420-014-1008-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health-related quality of life among residents with and without COPD in a historically industrialised area

Abstract: PurposeChronic obstructive pulmonary disease (COPD) is associated with substantial morbidity, including impaired health-related quality of life (HRQoL). Despite the prominent role of occupational factors in the aetiology of COPD, the relationship between these exposures and HRQoL has not been well elucidated.MethodsA subpopulation from an epidemiological study, designed to assess the workplace contribution to COPD, was administered the EQ5D HRQoL tool. Demographics, an index of economic deprivation, health end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Compared with others, are persons with COPD and a burden of past occupational exposure at increased risk of greater disease severity, accelerated decline in function, more frequent disease exacerbation, higher rates of healthcare utilisation, or poorer quality of life? Studies exploring some of these questions do raise the possibility that COPD-associated disability may indeed be greater among those with work-related disease 11 13. Such findings, if confirmed, have important implications for patient care and for social insurance compensation schemes.…”
mentioning
confidence: 97%
“…Compared with others, are persons with COPD and a burden of past occupational exposure at increased risk of greater disease severity, accelerated decline in function, more frequent disease exacerbation, higher rates of healthcare utilisation, or poorer quality of life? Studies exploring some of these questions do raise the possibility that COPD-associated disability may indeed be greater among those with work-related disease 11 13. Such findings, if confirmed, have important implications for patient care and for social insurance compensation schemes.…”
mentioning
confidence: 97%
“…Some studies reported lower mortality rates for females [32][33][34], while others found no difference [35][36][37][38]. Only two models specified quality of life by gender, while several studies found a lower quality of life for female patients [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Health-related quality of life (HRQoL) shows physical, cognitive, emotional, and social aspects measured by questionnaires, and evaluates the effect of a disease, disability, or disorder on individual's life quality [10]. Until now, a lot of HRQoL questionnaires have been developed and are used to evaluate life quality in patients with various diseases or disabilities [11][12][13][14], in which there are two types of instruments-specific instruments and generic instruments. As a generic measure, European quality of life-5 dimensions (EQ-5D) was developed by the EuroQol Group to evaluate [15].…”
Section: Introductionmentioning
confidence: 99%